Neurosurgical intervention in ultra-severe closed traumatic brain injury: Is it worth the effort? - Nikolaos Gkantsinikoudis; Iftakher Hossain; Niklas Marklund; Parmenion P. Tsitsopoulos (Brain and Spine)
Introduction: A subgroup of severe Traumatic Brain Injury (TBI) patients, known as ultra-severe (us-TBI), is most commonly defined as a post-resuscitation Glasgow Coma Scale (GCS) of 3–5. There is uncertainty on whether these critically injured patients can benefit from neurosurgical intervention. Research question: The available evidence regarding the decision-making and outcome following management of us-TBI patients is critically reviewed. Material and methods: Selected databases (PubMed, Google Scholar, Scopus and Cochrane Library) were searched from 1979 to May 2024 for publications on us-TBI patients, with a focus on treatment strategy, mortality and functional outcomes. Inclusion criteria were adult patients >18 years old with closed head trauma and admission post-resuscitation GCS 3–5. Studies were independently assessed for inclusion by two reviewers, and potential disagreements were solved by consensus. Results: Where such data could be extracted, mortality rate was 27–100%, and favorable outcome was observed in 4–30% of us-TBI patients. While early aggressive neurosurgical management was associated with decreased mortality, a high proportion of patients survived with unfavorable functional status. Discussion and conclusion: With supportive care only, outcome of patients with us-TBI is almost universally poor. Early and aggressive neurosurgical intervention in addition to best medical management can lead to favorable functional outcome in selected cases particularly in younger patients with an initial GCS>3 and traumatic mass lesions. There is insufficient data regarding the effectiveness of neurosurgical management on the outcome of us-TBI patients. and the decision to initiate treatment should be based on an individual basis.